Nilai Perusahaan Badan Usaha Milik Negara selama Pandemi Covid-19 - Hwihanus Hwihanus (Owner : Riset dan Jurnal Akuntansi, 2022)
The uniqueness of BUMN is that the ownership of BUMN is in the hands and regulated by the government and is an attraction for investors to invest their capital. Investors believe that BUMN stock prices will provide high value in the midst of economic, political, and social shocks including the COVID-19 pandemic that has hit Indonesia since March 2020 now and has undermined the performance of company management that has been built since the company was founded. This research is to see how much company value is generated during the Covid-19 Pandemic from management performance in managing owner wealth, investment decisions, and macroeconomic conditions and their effect on investors in State-Owned Enterprises. The non-random sampling technique was used in 20 SOEs from 25 companies by ignoring banking SOEs listed on the Indonesia Stock Exchange in 2020. The analysis technique used Partial Least Square consisting of the Inner model, Outers model, and Weight. connection. The results show that macro fundamentals have a significant and negative effect on financial performance (H3); ownership structure has a positive and significant effect on firm value (H7) and funding decisions have a negative and significant effect on financial performance (H8). The results of the test of firm value are not only determined from macro fundamental variables, investment decisions, ownership structure, and performance but there are other variables outside the variables being tested.